ImProving Outcomes after STroke (POST): results from the randomized clinical pilot trial. Issue 8 (18th October 2012) - Hackett, Maree L.; Carter, Greg; Crimmins, Denis; Clarke, Tracy; Arblaster, Lucy; Billot, Laurent; Mysore, Jayanthi; Sturm, Jonathan
<x xml:space="preserve">Abstract</x> Background One in three patients experience depression after stroke. An effective strategy to prevent depression after stroke that could be economically delivered to most patients with a low likelihood of adverse events is needed. Methods In a randomized trial conducted in New South Wales, Australia, a postcard was sent monthly to participants (n = 100) for five‐months following hospital discharge after stroke (plus usual care) and compared with usual care (n = 101). Ethical approval was obtained to withhold information about the intervention and primary outcome from participants during the consent process. Results No significant difference was seen in the proportion of participants with depression in the intervention group (1/88) vs. the control group (3/76) (relative risk 0·29, 95% confidence interval 0·03–2·71) at six‐months. No significant differences were seen on Hospital Anxiety Depression Scale (HADS) depression and anxiety sub‐scale scores, quality of life, or activities of daily living; however, many (47/100) responded positively to the postcards. Conclusions Although this simple postcard intervention did not significantly reduce the proportion of participants experiencing high HADS depression sub‐scale scores after stroke, it may be an effective way to engage with people after stroke following hospital discharge.